Emerging Role of Lymphatics in the Regulation of Intestinal Lipid Mobilization - Xiao, Changting; Stahel, Priska; Nahmias, Avital; Lewis, Gary F. (Frontiers in Physiology, 2020)
Intestinal handling of dietary triglycerides has important implications for health and disease. Following digestion in the intestinal lumen, absorption and re-esterification of fatty acids and monoacylglycerols in intestinal enterocytes, triglycerides are packaged into lipoprotein particles (chylomicrons) for secretion or into cytoplasmic lipid droplets for transient or more prolonged storage. Despite the recognition of prolonged retention of triglycerides in the postabsorptive phase and subsequent release from the intestine in chylomicron particles, the underlying regulatory mechanisms remain poorly understood. Chylomicron secretion involves multiple steps, including intracellular assembly and post-assembly transport through cellular organelles, the lamina propria and the mesenteric lymphatics before being released into the circulation. Contrary to the long-held view that the intestinal lymphatic vasculature acts mainly as a passive conduit, it is increasingly recognized to play an active and regulatory role in the rate of chylomicron release into the circulation. Here we review the latest advances in understanding the role of lymphatics in intestinal lipid handling and chylomicron secretion. We highlight emerging evidence that oral glucose and the gut hormone glucagon-like peptide-2 mobilize retained enteral lipid by differing mechanisms to promote the secretion of chylomicrons, glucose possibly by mobilizing cytoplasmic lipid droplets and glucagon-like peptide-2 possibly by targeting post-enterocyte secretory mechanisms. We discuss other potential regulatory factors that are the focus of ongoing and future research. Regulation of lymphatic pumping and function is emerging as an area of great interest in our understanding of the integrated absorption of dietary fat and chylomicron secretion and potential implications for whole-body metabolic health.